SIMPLE SELF-CONFRONTATION AS A TOOL FOR ANALYSING THE OBSTACLES AND DEVELOPMENTS OF DIDACTIC ACTION IN THE FRENCH CLASSROOM - Thierno LY (Universitaria Publishing House, Craiova, 2021)
This article raises the question of the strategies developed by teachers in situations faced with relative and/or consecutive modifications of the cognitive context of didactic interactions, that means the environment. Thus, the simple selfconfrontation would be a tool to analyse the impediments and developments of the activity (Wittorski, 2010; Cattonar, Lessard & Maroy, 2010). Through the discourse of simple self-confrontation, in which the teacher dialogues with himself and is surprised by his actions in the didactic environment, it is possible for him to analyse his initial activity and to develop a posteriori professional skills drawn from his experiential experience.